Cell Cycle Regulation in the Plant Response to Stress - Qi, Feifei; Zhang, Fuxin (Frontiers in Plant Science, 2020)
As sessile organisms, plants face a variety of environmental challenges. Their reproduction and survival depend on their ability to adapt to these stressors, which include water, heat stress, high salinity, and pathogen infection. Failure to adapt to these stressors results in programmed cell death and decreased viability, as well as reduced productivity in the case of crop plants. The growth and development of plants are maintained by meiosis and mitosis as well as endoreduplication, during which DNA replicates without cytokinesis, leading to polyploidy. As in other eukaryotes, the cell cycle in plants consists of four stages (G1, S, G2, and M) with two major check points, namely, the G1/S check point and G2/M check point, that ensure normal cell division. Progression through these checkpoints involves the activity of cyclin-dependent kinases and their regulatory subunits known as cyclins. In order for plants to survive, cell cycle control must be balanced with adaption to dynamic environmental conditions. In this review, we summarize recent advances in our understanding of cell cycle regulation in plants, with a focus on the molecular interactions of cell cycle machinery in the context of stress tolerance.